SEPTORIA ALBANIENSIS THUEM. CAUSING LEAF SPOT OF SALIX TRIANDRA IN IRAN (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
Septoria collections on Salix spp. from herbarium of Iranian Research Institute of Plant Protection were studied. The collections were identified on the base of morphometric criteria. This study results to identify Septoria didyma Fuckel, Septoria capreae Westend., Septoria albaniensis Thuem. This is the first report of Septoria albaniensis Thuem. for Iranian mycoflora.
Keywords: $Septoria$ collections on $Salix$ spp.; morphometric criteria; Iranian mycoflora